2019
DOI: 10.3390/v11060559
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Interleukin Enhancer-Binding Factor 2, ILF2, Inhibits Japanese Encephalitis Virus Replication In Vitro

Abstract: Japanese encephalitis virus (JEV) is a zoonotic mosquito-borne flavivirus which is the leading causative agent of viral encephalitis in endemic regions. JEV NS3 is a component of the viral replicase complex and is a multifunctional protein. In this study, interleukin enhancer-binding factor 2 (ILF2) is identified as a novel cellular protein interacting with NS3 through co-immunoprecipitation assay and LC-MS/MS. The expression of ILF2 is decreased in JEV-infected human embryonic kidney (293T) cells. The knockdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Among the BmTCTP interactions, it was shown that BmILF, the only one immune molecule, is able to interact with TCTP-WT but not with TCTP-K164R, which gives us an exciting clue to understand the immunity function of BmTCTP. The human ILF homologue has been demonstrated as an important host cellular protein that exerts a negatively regulatory effect on the replication of various viruses (53,55,57). Our result also showed that overexpression of the silkworm BmILF significantly inhibited virus replication.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Among the BmTCTP interactions, it was shown that BmILF, the only one immune molecule, is able to interact with TCTP-WT but not with TCTP-K164R, which gives us an exciting clue to understand the immunity function of BmTCTP. The human ILF homologue has been demonstrated as an important host cellular protein that exerts a negatively regulatory effect on the replication of various viruses (53,55,57). Our result also showed that overexpression of the silkworm BmILF significantly inhibited virus replication.…”
Section: Discussionsupporting
confidence: 62%
“…Indeed, previous studies have demonstrated that human interleukin enhancer binding factor 2 (ILF2) is considered as an important host cellular protein, which exerts a negatively regulatory effect on the replication of various viruses, such as human immunodeficiency virus type 1 (HIV-1), porcine reproductive and respiratory syndrome virus (PRRSV), and Japanese encephalitis virus (JEV) (53)(54)(55)(56)(57). To further characterize the correlation between BmTCTP and BmILF and whether the silkworm BmILF was able to regulate BmNPV replication, we investigated their functions in the response to BmNPV infection.…”
Section: Bmtctp Regulated Bmilf Expression and Inhibited Viral Replic...mentioning
confidence: 99%
“…The expression profiles of immune-related genes, including the IL-1β , IL-8 , IL-10 , TNF-α , ALF and TOR of L. vannamei fed with CpG 1826, CpG 1681, CpG 2006, CpG 8954, CpG M362, CpG 1585, and CpG 2143 exhibited significant upregulation. An interleukin ( IL ) system is essential for the proper regulation of T cell proliferation accompanied with an antigen encounter, as well as the modulation of apoptosis ( 39 ). Additionally, the IL family was well documented in invertebrates for its crucial roles in regulating innate immune system, such as in Chinese mitten crab ( 40 ) and in L. vannamei ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ILF2/ILF3 complex is a crucial regulatory factor involved in apoptosis [ 14 ], DNA repair [ 15 ], gene transcription [ 16 ], microRNA processing [ 17 , 18 ], mRNA translation [ 19 ], and host defense [ 20 ]. In addition, the ILF2/ILF3 heterodimer was reported to regulate the replication process of numerous viruses, such as hepatitis C virus [ 21 ], infectious bursal disease virus (IBDV) [ 22 ], poliovirus [ 23 ], influenza virus [ 24 ], dengue virus [ 25 ], human immunodeficiency virus type 1 [ 26 ], human T-cell leukemia virus [ 27 ], porcine reproductive and respiratory syndrome virus (PRRSV) [ 28 ], and Japanese encephalitis virus [ 29 ]. Interestingly, ILF2 functions as both a negative regulator [ 28 , 29 ] and a positive regulator [ 26 ] in the viral replication process.…”
Section: Introductionmentioning
confidence: 99%